2015
DOI: 10.1007/s00059-015-4392-2
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine improves exercise tolerance in patients with ischemic heart disease

Abstract: Addition of TMZ to standard treatment significantly improved exercise tolerance in patients with IHD, and IHD patients with HF may experience even more benefits. However, there is insufficient evidence to show that TMZ has beneficial effects in participants with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…Three meta-analyses of the available data suggest that Trimetazidine improves symptoms, exercise capacity and prognosis in patients with HFrEF. [40][41][42] The effect of trimetazidine on exercise capacity and symptoms are concordant in all studies and suggest an additive effect on top of medical therapy and on top of cardiac rehabilitation programmes. (Figure 7 and 8) It has been observed that trimetazidine improves skeletal muscle metabolism.…”
Section: Metabolic Agentsmentioning
confidence: 81%
“…Three meta-analyses of the available data suggest that Trimetazidine improves symptoms, exercise capacity and prognosis in patients with HFrEF. [40][41][42] The effect of trimetazidine on exercise capacity and symptoms are concordant in all studies and suggest an additive effect on top of medical therapy and on top of cardiac rehabilitation programmes. (Figure 7 and 8) It has been observed that trimetazidine improves skeletal muscle metabolism.…”
Section: Metabolic Agentsmentioning
confidence: 81%
“…Целью исследования Zhao Y, et al [22] являлась оценка влияния ТМЗ в дополнение к стандартной лекарственной терапии на толерантность к физиче-ской нагрузке у больных с ИБС. С помощью система- Таким образом, в совокупности, после хрониче-ского введения TMЗ наблюдалось уменьшение сред-него количества приступов стенокардии в неделю, эпизодов безболевой ишемии миокарда, снижение среднего еженедельного потребления нитратов короткого действия и улучшение качества жизни [23].…”
Section: место в терапии клинические исследованияunclassified
“…Добавление триметазидина к стан-дартной терапии больных с сочетанием ИБС и хрониче-ской сердечной недостаточности в еще большей степени повышало толерантность к физической нагрузке [24], сопровождалось снижением частоты смертельного исхода от всех причин на 71% (p < 0,00001), сердечно-сосудистых осложнений и госпитализаций -на 58% (р < 0,00001) [25]. В качестве дополнения к традиционной антиангинальной Примечание.…”
Section: ишемическая болезнь сердцаunclassified